Pengaruh Tax Planing dan Tunneling Incentive terhadap Tindakan Transfer pricing dengan Kualitas Audit Sebagai Variable Moderasi: Study Pada Perusahaan Tambang yang Terdaftar di BEI - Dicky Aditya; Hexana Sri Lastanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Transfer pricing and tunneling practices in large corporations are critical issues in tax management and corporate governance. Transfer pricing manipulates profits to reduce tax liabilities, negatively impacting state revenues. The Adaro case study illustrates how transfer pricing minimizes tax obligations in Indonesia, potentially causing annual state revenue losses of US$ 14 million. Tunneling involves transferring company assets or profits for the personal gain of majority shareholders, often at the expense of minority shareholders. Research indicates tunneling incentives can drive transfer pricing. Financial audits are crucial in uncovering these unethical practices, ensuring transparent and accurate information to external stakeholders. Enhanced oversight and effective auditing are essential to address these issues, maintaining tax system integrity and corporate governance.